2017
DOI: 10.1159/000477159
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cataract Progression after Nd:YAG Vitreolysis for Vitreous Floaters: A Case Report and Literature Review

Abstract: Purpose: We report a case of rapid cataract progression after Nd:YAG vitreolysis for vitreous floaters. Case Report: A 55-year-old man presented with acute onset of blurred vision following Nd:YAG vitreolysis for symptomatic floaters in the left eye. His initial best corrected visual acuity (BCVA) was 20/1,000 in the left eye. Ocular examinations showed frost-like opacities of the lens and a suspected break of the posterior capsule in the left eye. There were no detectable retinal lesions. Cataract surgery was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…The documented complications in a few small case series and individual case reports include transient elevation of IOP, focal posterior capsular opacities, refractory glaucoma, minor retinal hemorrhage, retinal breaks with detachment, cystoid macular edema, and so on. Recent studies by Noristani et al [19], Koo et al [20], and Sun et al [6], respectively, described cataract, especially posterior capsular cataract with loss of integrity as a potential complication of the treated eye. It was analyzed that an inadvertent delivery of the laser power anterior to the designated target in the vitreous and the inadequate distance of the focus from the crystalline lens were responsible for the development of cataracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The documented complications in a few small case series and individual case reports include transient elevation of IOP, focal posterior capsular opacities, refractory glaucoma, minor retinal hemorrhage, retinal breaks with detachment, cystoid macular edema, and so on. Recent studies by Noristani et al [19], Koo et al [20], and Sun et al [6], respectively, described cataract, especially posterior capsular cataract with loss of integrity as a potential complication of the treated eye. It was analyzed that an inadvertent delivery of the laser power anterior to the designated target in the vitreous and the inadequate distance of the focus from the crystalline lens were responsible for the development of cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, more patients suffering from symptomatic vitreous floaters have clinically managed to get rid of the symptoms [4, 5]. As a potent noninvasive treatment modality for floaters, neodymium-doped yttrium aluminum garnet (Nd:YAG) laser vitreolysis is considered as a safe procedure with minimal complications [6]. Nd:YAG laser excites short, intense pulses and produces energy to vaporize the vitreous opacities to plasma by raising the reginal temperature to above 1000 Kelvin at a confined spot [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to retinal [9,38,39] or crystalline lens and posterior capsule damage [9][10][11][12]39], the occurrence of refractory open-angle glaucoma has been reported after YAG laser vitreolysis for floaters [9,13]. Cowan and coauthors reported the cases of 3 eyes (2 patients) that underwent YAG laser vitreolysis for floaters and eventually suffered chronic open angle glaucoma after sustaining very high intraocular pressures ([ 40 mmHg) [13].…”
Section: Yag Laser Treatment Of Vitreous Floatersmentioning
confidence: 99%
“…In recent years, neodymium-doped yttrium-aluminum-garnet (YAG) laser vitreolysis has gained significant popularity [5,6], as the technique offers a fast, relatively inexpensive, non-incisional therapeutic option for the treatment of vitreous floaters. However, the publication of studies showing conflicting results [7,8] and potentially sight-threatening complications [9][10][11][12][13] have fueled dispute and may have prevented the widespread adoption of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that Nd:YAG laser vitreolysis caused cataract formation with posterior capsule defects in our patient. This complication has been recently reported in three patients . It is not clear if the cataract and associated posterior capsule injury occur due to inadvertent focusing of the laser beam adjacent to the posterior capsule or by another mechanism.…”
mentioning
confidence: 94%